Exposures to environmental phenols in Southern California firefighters and findings of elevated urinary benzophenone-3 levels. (March 2016) - Waldman, Jed M.; Gavin, Qi; Anderson, Meredith; Hoover, Sara; Alvaran, Josephine; Ip, Ho Sai Simon; Fenster, Laura; Wu, Nerissa T.; Krowech, Gail; Plummer, Laurel; Israel, Leslie; Das, Rupali; et al.
Abstract: Firefighters are at increased risk for exposure to toxic chemicals compared to the general population, but few studies of this occupational group have included biomonitoring. We measured selected phenolic chemicals in urine collected from 101 Southern California firefighters. The analytes included bisphenol A (BPA), triclosan, benzophenone-3 (BP-3), and parabens, which are common ingredients in a range of consumer products. BP-3, BPA, triclosan, and methyl paraben were detected in almost all study subjects (94–100%). The BP-3 geometric mean for firefighters was approximately five times higher than for a comparable National Health and Nutrition Examination Survey (NHANES) subgroup. Demographic and exposure data were collected from medical records and via a questionnaire, and covariates were examined to assess associations with BP-3 levels. BP-3 levels were elevated across all firefighter age groups, with the highest levels observed in the 35 to 39 year old group. Body fat percentage had a significant inverse association with BP-3 concentrations. Our results indicate pervasive exposure to BP-3, BPA, triclosan, and methyl paraben in this population of firefighters, consistent with studies of other populations. Further research is needed to investigate possible explanations for the higher observed BP-3 levels, such as occupational or California-specific exposures. Highlights: We measured urinary environmental phenols in Southern California firefighters. Benzophenone-3 (BP-3) was found in 100% of study subjects. The BP-3 geometric mean in firefighters was about 5 times higher than NHANES males. BP-3 concentrations were inversely associated with body fat percentage.